Fertilizer prescription for target yield of wheat (Triticum aestivum) in alluvial soils - SINGH, JAGDEEP; MAVI, M S; SAINI, SAT PAL (The Indian Journal of Agricultural Sciences, 2022)
Soil test crop response correlation studies were carried out to establish target yield prescription equations for wheat (Triticum aestivum L.) under the Integrated Plant Nutrition System (IPNS) at Research Farm of Punjab Agricultural University, Ludhiana, Punjab during 2019–2021. Fertilizer prescriptions under NPK alone and IPNS were developed for wheat crops using Ramamoorthy’s “Inductive cum Targeted yield approach”. The amount of nutrients needed for producing 100 kg of wheat were 2.06, 0.78, and 1.95 kg/q of N, P2O5 and K2O, respectively. The nutrients contributed by soil and fertilizer were found to be 52.3% and 54% N, 11.7% and 50% P, and 20.2% and 20.6% K, respectively. Likewise, the organic material in the form of rice residue incorporation contributed 42.0% N, 15.3% P, and 26.0% K and increased the nutrient (N, P and K) uptake. The incorporated rice residue increased the soil organic carbon and microbial population substantially resulting in more mineralization thereby increasing nutrient availability. Therefore, the site-specific targeted yield-based approach used for developing fertilizer prescription equations gives a shred of strong evidence for maintaining soil health with higher crop yields and efficient nutrient management.